Effects of alkyl chain number and position on 2D self-assemblies. Issue 51 (26th June 2017) - Hu, Yi; Miao, Kai; Xu, Li; Zha, Bao; Miao, Xinrui; Deng, Wenli
Abstract : Alkyl chain number and position effects are explored via the fabrication and regulation of 2D self-assemblies at liquid/HOPG interfaces. Abstract : Utilizing the effects of alkyl chain number and position is an efficient strategy for the fabrication and regulation of diverse self-assembly structures. Based on self-assembling behavior, we explored these two effects with regard to the self-assembly mechanism and thermal, spectral, and crystal analysis. Eight types of anthraquinone derivatives were used, with eight different self-assembly configurations observed at the 1-octanoic acid/HOPG interface, namely six linear structures, one zigzag structure, and one dimer-linear structures. As these anthraquinone derivatives possess different molecular symmetries, which can affect the molecular dipole, the formation mechanism of these self-assembled networks was investigated with regard to dipole–dipole interactions. Furthermore, density functional theory calculations showed that an increasing alkyl chain number led to a rise in intermolecular van der Waals interactions. However, despite the variation in alkyl chain number and position, the strength of hydrogen bonds between the anthraquinone cores was particularly dependent on the assembled structure. This work provides a comprehensive method for fabricating self-assemblies at liquid/solid interfaces in 2D crystal engineering, and we believe it will be of significance toward studying the effects of alkyl chain number and position on structural diversity in supramolecular chemistry.